Use of qualitative and quantitative microbial data to determine if turkey re-hang and post-chill sampling are predictive of Salmonella enterica contamination in ground turkey - Paredes Rivera, Mariana Beatriz (My University, 2025)
Salmonella is a major foodborne pathogen posing significant economic and public health risks worldwide. Poultry products serve as its primary reservoir, making the consumption of contaminated poultry a leading cause of salmonellosis. To mitigate this risk, the U.S. Department of Agriculture Food Safety Inspection Services (USDA-FSIS) has progressively strengthened the Salmonella Regulatory Framework for Raw Poultry Products since 1996. Currently, industry stakeholders are required to monitor microbial indicators at re-hang and post-chill as a means of assessing processing control. However, numerous studies have demonstrated that Salmonella prevalence in final products, such as ground meat, cannot be reliably predicted from these sampling locations, therefore, the efficacy of re-hang and post-chill sampling assessing Salmonella in ground turkey remains uncertain. This study aimed to evaluate the effectiveness of microbial sampling to measure Salmonella in ground turkey by quantifying microbial indicators and detecting Salmonella at key processing steps: re-hang, post-chill, and grinding. A total of 455 samples were collected from 40 commercial turkey barns at a poultry processing facility (re-hang = 200, post-chill = 200, and grinding = 55 samples). Indicator microorganisms, including Aerobic Plate Counts (APC), Enterobacteriaceae (EB), E. coli, and Salmonella were detected and quantified using different methods. Significant differences (P<0.0001) were observed among sampling locations, depicting high levels for all indicator microorganisms at re-hang, a systematic reduction after post-chill, and re-emergence at grinding. Salmonella detection was significantly higher in ground samples (30.97%) compared to re-hang and post-chill samples (6.19% and 3.1% respectively). Furthermore, no relationship (P>0.05) was observed between Salmonella presence and microbial indicators at any sampling location. While strong positive association were identified between re-hang and post-chill indicator counts (P<0.0001), poor linear regressions were observed between re-hang and grinding, as well as post-chill and grinding (P>0.05). These findings suggest that relying solely on microbial indicator quantification is insufficient for risk assessment of final product safety. Process control measures based on indicator microorganisms does not accurately reflect Salmonella contamination in ground turkey, highlighting the need for more robust pathogen-specific detection strategies.
Keywords: Salmonella enterica; Indicator microorganisms; Process control; Re-hang; Post-chill; Ground turkey